(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2021)
The results of monitoring of the spontaneous vegetation in several leading institutions of the Right Bank of Ukraine are presented. It is M.M. Gryshko National Botanical Garden of the National Academy of Sciences of Ukraine (Kyiv), State Dendrological Park «Oleksandriya» of the National Academy of Sciences of Ukraine (Bila Tserkva) and Syretsky Dendrological Park of National Importance (Kyiv). The studies were conducted in 2020–2021. 82 new taxa (species and subspecies) was found in the wild on the territory of the M.M. Gryshko National Botanical Garden. Currently, the historical spontaneous flora of the garden includes 730 taxa (species and subspecies), of which 418 – native, 173 – escaped plants, 139 – xenophytes. Rare native plants Hieracium sabaudum subsp. virgultorum, Pilosella plicatula, Taraxacum scanicum, Tragopogon ucrainicus were found during the monitoring of the habitats. Dysphania ambrosioides, Epilobium ciliatum subsp. adenocaulon, Erechtites hieracifolia, Erigeron strigosus, Euphorbia maculata, Hordeum bulbosum, Lamium amplexicaule var. orientale were important as progressive xenophytes. Arum elongatum, A. maculatum, Castanea sativa, Muscari armeniacum, Ornithogalum boucheanum has high rates of naturalization as a new ergasiophytes. For the first time, there are information on at least 20 introduced plants that have spread outside the botanical garden to the adjacent territories of Kyiv. Eighteen new taxa, including the endemic species Myosotis ucrainica, have been identified in the territory of park «Oleksandriya». According to new data, the wild flora of the arboretum includes 850 taxa, of which 581 native and 269 alien. Four species that were considered extinct were identified. Two natural habitats the Red Book species Neottia nidus-avis and Stipa pennata were found. There are information about mainly adventive plants in the spontaneous flora for the Syretsky Dendrological Park. Eleven tree ergasiophytes were found in the valley of the Kuryachy Brid stream near the Syretsky Dendrological Park. Among them, Fagus sylvatica, Lonicera xylosteum, Rubus occidentalis, Taxus baccata are extremely important for future monitoring.